GosB Inhibits Triacylglycerol Synthesis and Promotes Cell Survival in Mouse Mammary Epithelial Cells. (17th October 2017) - Xu, Gaoxiao; Duan, Saixing; Hou, Jianye; Wei, Zhongxin; Zhao, Guangwei
Abstract : It has been demonstrated that the activator protein related transcription factor Finkel-Biskis-Jinkins murine osteosarcoma B (GosB) is involved in preadipocyte differentiation and triacylglycerol synthesis. However, the role of GosB in regulating the synthesis of milk fatty acid in mouse mammary glands remains unclear. This research uncovered potentially new roles of GosB in suppressing milk fatty acid synthesis. Results revealed that GosB had the highest expression in lung tissue and showed a higher expression level during nonlactation than during lactation. GosB inhibited the expression of fatty acid synthase (FASN), stearoyl-CoA desaturase (SCD), fatty acid binding protein 4 (FABP4), diacylglycerol acyltransferase 1 (DGAT1), perilipin 2 (PLIN2), perilipin 3 (PLIN3), and C/EBPα in mouse mammary gland epithelial cells (MEC). In addition, GosB reduced cellular triglyceride content and the accumulation of lipid droplets; in particular, GosB enhanced saturated fatty acid concentration (C16:0 and C18:0). The PPAR γ agonist, rosiglitazone (ROSI), promoted apoptosis and inhibited cell proliferation. GosB increased the expression of Bcl-2 and protected MEC from ROSI-induced apoptosis. Furthermore, MECs were protected from apoptosis through the GosB regulation of intracellular calcium concentrations. These findings suggest that GosB may regulate mammary epithelial cells milk fat synthesis and apoptosis via PPAR γ in mouse mammary glands.